DEVELOPING CHILDREN'S IMAGINATION THROUGH THE STORY METHOD - Miftahul Jannah; Ahmad Fajian; Husin; Rizka Maulida; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Nowadays there are many visual media or other media that influence children's imagination. Which causes a decrease in children's imagination. The child's imagination begins to decline, this is due to the existence of visual media that makes it easier for someone to tell a story through several pictures, or to show the events of a story directly. This study aims to develop children's imagination of stories read, heard, or stories told by someone, and direct them in a positive direction, not in a negative direction. The research method used is the library research method or library research. The results obtained from this study are that a child's imagination can be developed using the story method with a variety of structured stories, using language that is easy to understand, attractive illustrations and designed in such a way. And there are several things that need attention in the story so that it is in a positive direction and not in a negative direction. In developing a child's imagination, it is necessary to pay attention to several things related to the child's imagination, such as the characteristics of the child and some stories that do not contain elements of a sad story.